Prototype Sistem Kontrol Pengaturan Suhu Pemberian Pakan Serta Pembersihan Kotoran Ayam Berbasis Arduino - Pebriansyah, Defta; Dwi Saputra, Rinaldi; Surojo, Surojo; Priestiani, Priestiani (Jurnal Inovasi Teknologi Terapan, 2024)
Livestock farming is one of five agricultural subsectors. Animal husbandry is the activity of keeping livestock for cultivation and gaining profits from this activity. Broiler chickens are a type of commodity in the livestock sector that produces food from livestock and has quite potential economic value. The aim of this research is to help breeders' activities in controlling and monitoring livestock continuity. Apart from that, this research is also to produce ideal temperatures in the chick cage so that heat stress conditions do not occur in the chicks. Based on the sensor and thermometer test results for temperature measurements in the table, it can be concluded that the average percentage of measurement results is normal. The data that has been taken shows that the LM35 and DHT11 sensors have good temperature detection capabilities. Therefore, this sensor can be used well to detect the temperature needed in this final project.